MANAGING FINANCIAL RESOURCES IN IMPROVING THE QUALITY OF EDUCATION AT MADRASAH ALIYAH NEGERI SINTANG - Marzuki Marzuki (Jurnal Konseling Pendidikan Islam, 2025)
This research explores the role of financial resource management financial resources in improving the quality of education in Madrasah Aliyah Negeri Sintang. Through the literature study method, this research investigates education policy, community participation, and fund management efficiency as key elements in madrasah financial resource management. as key elements in madrasah financial resource management. Results results show that education policies that are integrated with financial regulations support a more efficient allocation of funds, while community participation provides additional support and improves transparency. The efficiency of fund management is a key focus to ensure the optimal use of financial resources in improving infrastructure, facilities, and the quality of educators. The research also identified challenges in managing financial resources, including limited budget limitations and a lack of understanding of financial regulations. As a solution, strategic suggestions were provided, including improving education policies, increasing community participation, and improving managerial capacity. Implications of this research bring a deep understanding of the complexity of managing financial resources in Madrasah.